Uniformly high-order schemes on arbitrary unstructured meshes for advection diffusion - Titarev, Vladimir A.; Drikakis, Dimitris (Elsevier, 2011)
The paper presents a linear high-order method for advection-di®usion conser- vation laws on three dimensional mixed-element unstructured meshes. The key ingredient of the method is a reconstruction procedure in local compu- tational coordinates. Numerical results illustrate the convergence rates for the linear equation and a non-linear hyperbolic system with di®usion terms for various types of meshes.
Keywords: unstructured; tetrahedral; hexahedral; prismatic; pyramidal; mixed-element; very high-order; di®usive